Rescheduling Pembiayaan Bermasalah Di KSPPS BMT Mandiri Sejahtera Cabang Dukun - Imtiyaz, Nakhwah Bahirotul; Arifin, Sirajul (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the implementation of rescheduling in handling problematic financing at KSPPS BMT Mandiri Sejahtera Dukun Branch. The research employed a qualitative method with a descriptive approach to gain an in-depth understanding of the strategies used by the institution to overcome financing problems. Data were collected through interviews with the Branch Manager and Account Officer, as well as through an analysis of financing collectability data from March 2024 to March 2025. Supporting data were also obtained through documentation and observation related to the financing management process within the institution. The results indicate that the main causes of problematic financing originate from weaknesses in the initial survey and analysis process of prospective members, as well as external factors such as crop failure and declining business activities of members. To address these issues, KSPPS BMT Mandiri Sejahtera Dukun Branch implements several strategies, including routine monitoring of financing members, intensive communication, and the application of rescheduling policies as the main instrument in financing restructuring. The implementation of rescheduling has proven to be effective and remains in accordance with Islamic financial principles. Based on financing collectability data, the quality of financing is relatively well maintained, with the Non-Performing Financing (NPF) ratio remaining below 5% in accordance with the standards set by financial authorities. Therefore, the implementation of rescheduling plays an important role in reducing problematic financing while maintaining the stability and sustainability of Islamic financial institutions.